Investigation of the microstructural fracture behaviour of asphalt mixtures using the finite element method. (10th December 2019) - Kollmann, Jonas; Liu, Pengfei; Lu, Guoyang; Wang, Dawei; Oeser, Markus; Leischner, Sabine
Highlights: Microstructural FE models were developed to simulate the asphalt mixtures. 2D CZM was applied to simulate the microscale crack initiation and propagation. Effects of temperature and air voids on fracture behaviour were investigated. Abstract: To limit and control the degradation of asphalt pavements and to increase the durability of the asphalt layers, a thorough understanding of the mechanical pavement response is necessary. As a contribution, it is imperative to investigate the fracture behaviours of asphalt mixtures. This paper applies two-dimensional (2D) cohesive zone modeling (CZM) techniques to simulate the microscale crack initiation and propagation within the asphalt mixtures. X-ray computed tomography (X-ray CT) scanning and digital image processing (DIP) techniques were applied to reconstruct the microstructure of asphalt specimens. Finite element (FE) simulations were conducted to simulate the quasi-static indirect tensile test (IDT) with the implementation of a 2D bilinear cohesive zone model. The FE models were optimised and validated based on experimental results. The validated model was then used to investigate the effect of temperature and the air voids on the fracture behaviour of asphalt mixtures. The results show that more significant damage is observed in broader areas outside of the main crack trajectory as the temperature is increased in the range considered in this study (−10 °C, 0 °C, +10 °C). The aggregate-mortar interface exhibited more significant damage than the bulk fracture within the mortar. The deformation voids which are defined as those not crossed by the final crack trajectory have no effect on the maximum reaction force at temperatures above 0 °C. Also, deformation voids are found to extend the time to failure. The results contribute to the current research on the fracture behaviour of asphalt mixtures and future investigations are recommended to facilitate the establishment of an asphalt mixture design method and evaluation method based on microscale failure mechanisms.